Persistent hepatitis C virus infection in a chimpanzee is associated with emergence of a cytotoxic T lymphocyte escape variant. - Weiner, A (1995)
Hepatitis C virus (HCV) establishes a persistent infection in humans and chimpanzees despite the presence of virus-specific, class I major histocompatibility complex-restricted CD8+ cytotoxic T lymphocytes (CTLs) in the liver. The data presented here demonstrate that CTLs directed against a conserved epitope in the HCV nonstructural 3 protein persist in the liver of a chronically infected chimpanzee for at least 2 years after infection. However, these CTLs did not recognize the HCV quasi-species present in the plasma of this animal at week 16 postinfection or at later time points. Escape from the CTL response was facilitated by an aspartic acid to glutamic acid (D-->E) substitution at amino acid position 1449 in all HCV genomes that were sequenced. The results of this study strongly support the concept that CTL responses can select for variant viruses with an enhanced ability to persist in a host and have important implications for the design of vaccines against HCV.